2019
DOI: 10.1002/jib.573
|View full text |Cite
|
Sign up to set email alerts
|

Aroma compounds in barrel aged apple distillates from two different distillation techniques

Abstract: The major fermentation and maturation related congeners in apple distillates from two different distillation techniques (alembic and column), matured in oak for 18 months, were measured by GC‐MS and HPLC. Together with a higher ethanol content, column distillates had higher ethyl acetate, methanol and n‐propanol levels compared with alembic distillates. A higher content of acetaldehyde was characteristic of the alembic distillates. The concentrations of i‐butanol, n‐butanol, amyl alcohols and n‐hexanol were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…In contrast, Coldea et al (2011) detected slightly higher concentrations of methanol in traditional plum and apple brandies from Romania, about 900-1000 g/hL a.a., depending on the fruit variety. Spaho et al (2019) demonstrated different methanol concentrations in apple distillate depending on the distillation apparatus used. Methanol concentrations were 540 and 830 g/hL a.a., respectively, for alembic and batch distillation column and decreased slightly during 18 months of aging in oak barrels.…”
Section: Methanol Content In Fruit Spiritsmentioning
confidence: 98%
“…In contrast, Coldea et al (2011) detected slightly higher concentrations of methanol in traditional plum and apple brandies from Romania, about 900-1000 g/hL a.a., depending on the fruit variety. Spaho et al (2019) demonstrated different methanol concentrations in apple distillate depending on the distillation apparatus used. Methanol concentrations were 540 and 830 g/hL a.a., respectively, for alembic and batch distillation column and decreased slightly during 18 months of aging in oak barrels.…”
Section: Methanol Content In Fruit Spiritsmentioning
confidence: 98%
“…Six out of eight apple cultivar spirits had the highest share of alcohols in their VOCs profile (Figure 1). The major higher alcohols in apple distillates are amylic alcohols, isobutyland n-propanol, accounting for approximately more than 90% of all higher alcohols in apple distillates [21,55]. The most abundant minor alcohol was phenylethyl, then 1-hexanol, 1-octanol, and benzyl alcohol.…”
Section: Volatile Organic Compounds In Apple Spiritsmentioning
confidence: 99%
“…The most common VOCs in distillates are major fermentative aroma compounds, which are produced during common and specific fruit fermentation. Investigations of major volatile compounds in apple and other fruit spirits have been conducted by numerous studies [18][19][20][21][22], while minor volatile compounds have been studied far less [23][24][25]. Minor volatile compounds are present in apple juice or cider in a very low concentration but have a significant influence on the overall sensory attribute [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional fruit brandy production still mostly uses a simple distillation pot. In recent years, column distillation has slowly entered the production of spirits in small distilleries and two different types of distillation equipment are now commonly used in the production of fruit spirits: the Charentais alembic pot (French style) and the batch distillation column (German style) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%